Gastroenterology, notes on its beginnings in the Central Region of Cuba - Ignacio Morales Martínez; Nancy Andreu Gómez (Acta Médica del Centro)
Introduction: Gastroenterology was not officially considered an independent specialty until after World War II. The creation, in 1932, of the Gastroenterology and Proctology section of the American Medical Association laid the foundations in this direction. The first Cuban Society of Gastroenterology dates back to 1922. Evidence of its practice is collected in the Central Region of Cuba around 1948. Objective: to specify the origin and development of Gastroenterology in the Central Region of Cuba. Methods: in this research, the historical method was followed, supported by the documentary review technique and interviews with key informants. Different documents were analyzed and methodological triangulation was carried out to arrive at integrative considerations. Development: a review is made of the main events related to the origin and consolidation of Gastroenterology in the Central Region of Cuba. Conclusions: Gastroenterology as a medical specialty has had an important development in the City of Santa Clara and has its main protagonist in the figure of Professor Oswaldo Carbó Bobia.